Acolhimento na percepção dos enfermeiros da atenção primária à Saúde - Marques-Ferreira, Maria de Lourdes da Silva [UNESP]; Barreira-Penques, Rosana Maria do Vale [UNESP]; Marin, Maria José Sanches [UNESP] (My University, 2014)
Objective: This paper is intended to explore how nurses working in primary health care perceive acceptance. Method: It is based on a qualitative study conducted through interviews with 21 nurses from eight municipalities in the State of São Paulo. A phenomenological approach was used in data analysis. Results: It was found that nurses' understanding of acceptance, at certain points in time, comes close to the principles and guidelines of the Unified Health System (SUS). Conclusions: Nursing professionals manifest difficulties with the structure, organization and management of health services and express actions and beliefs related to the traditional model of care. The various stakeholders need to join forces if acceptance is to be achieved.

Objetivo: el presente estudio se propone comprender la percepción de la acogida de los enfermeros que actúan en la Atención Primaria a la Salud. Método: es una investigación cualitativa realizada con entrevistas con 21 enfermeros de ocho municipios del interior del estado de São Paulo. El análisis de los datos se fundamentó en la vertiente fenomenológica, modalidad estructura del fenómeno. Resultados: se reveló que la comprensión de los enfermeros sobre la acogida, en algunos momentos, se aproxima de los principios y directrices del Sistema Único de Salud (SUS). Conclusiones: por otro lado, esos profesionales manifiestan dificultades con la estructura, organización y gestión de los servicios de salud y expresan acciones y creencias que se acercan al modelo tradicional de cuidado. Para la concreción de la acogida necesitan unir sus esfuerzos de los diferentes atores involucrados.

Objetivo: o presente estudo propõe-se a compreender a percepção de enfermeiros que atuam na Atenção Primária à Saúde sobre o acolhimento. Método: pesquisa qualitativa realizada a partir de entrevistas com 21 enfermeiros de oito municípios do interior paulista. A análise dos dados pautou-se na vertente fenomenológica, modalidade estrutura do fenômeno. Resultados: revelou-se que a compreensão dos enfermeiros sobre acolhimento, em alguns momentos, se aproxima dos princípios e diretrizes do SUS. Por outro lado, manifestam dificuldades com a estrutura, organização e gestão dos serviços de saúde, além de expressarem ações e crenças que se aproximam do modelo tradicional de cuidado. Conclusões: diante dos resultados, constata-se a união de esforços dos diferentes atores envolvidos no processo.
Acceptance in the perception of nurses involved in primary health care
Acogida en la percepción de los enfermeros de la atención primaria a la salud
Keywords: User embracement; Primary health care; Health system; Nursing; Nurses; Male; Acogimiento; Atención primaria de salud; Sistemas de salud; Enfermeira; Enfermeros; Acolhimento; Atenção primária à saúde; Sistemas de saúde; Enfermagem; Enfermeiros